2018
DOI: 10.1186/s13068-018-1010-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Yarrowia lipolytica to enhance lipid production from lignocellulosic materials

Abstract: BackgroundYarrowia lipolytica is a common biotechnological chassis for the production of lipids, which are the preferred feedstock for the production of fuels and chemicals. To reduce the cost of microbial lipid production, inexpensive carbon sources must be used, such as lignocellulosic hydrolysates. Unfortunately, lignocellulosic materials often contain toxic compounds and a large amount of xylose, which cannot be used by Y. lipolytica.ResultsIn this work, we engineered this yeast to efficiently use xylose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 30 publications
5
83
0
Order By: Relevance
“…The results obtained with crude xylose from SCB hydrolysate were highly encouraging. The yeast grew robustly (OD 600 : 25.3) on crude xylose despite the presence of AA and furfural at signi cant levels ( Figure 6B), in accordance with previous reports on agave hydrolysates [29]. The resultant SA concentration was 5.6 g/L with a yield of 0.14 g/g, which is similar to those obtained with pure xylose (0.19 g/g).…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained with crude xylose from SCB hydrolysate were highly encouraging. The yeast grew robustly (OD 600 : 25.3) on crude xylose despite the presence of AA and furfural at signi cant levels ( Figure 6B), in accordance with previous reports on agave hydrolysates [29]. The resultant SA concentration was 5.6 g/L with a yield of 0.14 g/g, which is similar to those obtained with pure xylose (0.19 g/g).…”
Section: Discussionsupporting
confidence: 89%
“…Y. lipolytica is considered to be a promising microbial workhorse for production of high value-added products [39,40]. In this study, we reported the development of quantitative measurement of violacein, based on both HPLC and microplate reader.…”
Section: Resultsmentioning
confidence: 99%
“…However, cells seem to prefer the alternative pathway of transketolase as it provides more carbon towards glycolysis and oxidative PPP, where the majority of NADPH is regenerated. The overexpression of phosphoketolase and phosphotransacetylase enzymes in Y. lipolytica resulted in 20-50% increased lipid production (Niehus et al, 2018). Therefore, the upregulation of phosphoketolase could be partially related to the increased accumulation of lipids and carotenoids at the aforementioned phases.…”
Section: Discussionmentioning
confidence: 99%